Jejak-Jejak Mistik di Balik Kesenian Bantengan Malang - Hermiawan, Nico (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2013)
Bantengan is a traditional dance in the city of Malang. Local people believe the Bantengan existence as an ancient art of ancestors which is still passed down through the generations until today. In the Landungsari village, Dinoyo, Malang, Bantengan dance is still well preserved by local residents. In this village, who still carry the ritual of Bersih Desa, live more than three groups of Bantengan. Bantengan dance performances cannot be separated from the magical elements that indicate when the players experienced trance. A very positive response from activists Bantengan (artist) and the enthusiasm of its spectators show that Bantengan is capable of being binding relationship between the local people with the universe surrounded them. This article is a small attempt to find a mystical element behind Bantengan dance that can be a unifying society. With the cultural strategy of C.A. van Peursen, we are invited to maintain the essence of our own culture and develop a cultural strategy to face the day of tomorrow.